Estime de soi, sentiment d’autoefficacité et intention de décrocher au collégial - Stéphane Thibodeau (Association Internationale de Pédagogie Universitaire, 2021)
For several years, the province of Quebec has been mobilizing to fight school dropouts. Because of the negative repercussions generates both at the individual and societal levels this growing phenomenon remains a major issue. The purpose of this study is to highlight the personal factors underlying school dropouts. More specifically, its purpose is to explore the relationships between self-esteem and intent to drop out among college students, as well as the role of self-efficacy on these relationships. Three hundred and ninety-one (391) students from three colleges (two public and one private) participated in the research. The French Canadian version of Bouffard et al. (2002) of Self-Perception Profile for Adolescents (SPPA, Harter, 1988), the teenager’s adaptation by Suldo and Shaffer (2007) of the Self-Efficacy Questionnaire for Children (SEQ-C, Muris, 2001) and the translation of the three items proposed by Hardre and Reeve (2003) allow to measure self-esteem, self-efficacy, and intent to drop out, respectively. The results suggest that college students' self-esteem and sense of efficacy are negatively related to intent to drop out. More specifically, the path analysis of the model presents adequate adjustment statistics of the model to the datas. It reveals indirect links between self-esteem and intent to drop out as well as the intermediary role of self-efficacy in these relationships., These results are discussed in light of the underlying theories as well as from previous studies.